Graft survival differences in kidney transplants related to recipient sex and age - Sancho, Asuncion; Gavela, Eva; Kanter, Julia; Beltrán, Sandra; Castro, Cristina; Escudero, Verónica; Pantoja, Jonay; Molina, Pablo; Vizcaíno, Belen; González, Mercedes; Calatayud, Emma; Avila, Ana (Frontiers in Medicine, 2022)
Background In recent years, there has been increasing interest in studying differences in recipient sex in renal disease treatment, access to renal replacement therapy and subsequent outcomes. Our aim was to find out whether there are differences in outcomes after renal transplantation between female and male kidney transplant recipients in our series, particularly in adults under 60 years of age during long-term follow-up. Methods Retrospective study of our kidney transplant series (n=1,101) to compare graft survival depending on the sex of the recipient in the entire series and in patients < 60 years (n=687) during long-term follow-up. Results We observed no association between recipient sex and graft survival throughout the series, regardless of recipient sex. However, adult female recipients under 60 years of age had lower graft survival than male recipients (p=0.040). Pre-transplant sensitization (HR 2.438, p=0.002) and donor age (HR: 1.021, P=0.017) were the independent variables associated with graft failure. Conclusions Female recipients younger than 60 years had lower graft survival than males, although there were no gender differences in graft or patient survival in the overall study population. Recipient sex per se was not related to graft failure, but greater immunological risk in females and more frequent use of expanded criteria donors in female recipients under 60 years of age were the main factors related to their poorer graft survival. Further studies and new strategies are needed to identify these differences and develop the best approach to address them.